Illness tracking in SARS-CoV-2 tested persons using a smartphone app: a non-interventional, prospective, cohort study. (March 2022) - Lovey, T.; Bielecki, M.; Gültekin, N.; Stettbacher, A.; Muggli, F.; Stanga, Z.; Farnham, A.; Deuel, J.; Schlagenhauf, P.
Abstract: There are few data on the range and severity of symptoms of SARS-CoV-2 infection or the impact on life quality in infected, previously healthy, young adults such as Swiss Armed Forces personnel. It is also unclear if an app can be used to remotely monitor symptoms in persons who test positive. Using a smartphone app called ITITP (Illness Tracking in Tested Persons) and weekly pop-up questionnaires, we aimed to evaluate the spectrum, duration, and impact of symptoms reported after a positive SARS-CoV-2 test according to sex, age, location, and comorbidities, and to compare these to responses from persons who tested negative. We followed up 502 participants (57% active participation), including 68 (13.5%) positive tested persons. Hospitalisation was reported by 6% of the positive tested participants. We found that positives reported significantly more symptoms that are typical of COVID-19 compared to negatives. These symptoms with odds ratio (OR > 1) were having difficulty breathing (OR 3.35; 95% CI: 1.16, 9.65; p = 0.03), having a reduced sense of taste (OR 5.45; 95% CI: 1.22, 24.34; p = 0.03) and a reduced sense of smell (OR 18.24; 95% CI: 4.23, 78.69; p < 0.001). Using a random forest model, we showed that tiredness was the single symptom that was rated as having a significant impact on daily activities, whereas the other symptoms, although frequent, had less impact. The study showed that the use of an app was feasible to remotely monitor symptoms in persons infected with SARS-CoV-2 and could be adapted for other settings and new pandemic phases such as the current Omicron wave.